The Main Square. Touristification and sociability in Los Cabos, Mexico: Plaza Antonio Mijares, 1974-2020 - Bojórquez Luque, Jesus; Pintor Sandoval, Renato (Universidad Pedagógica y Tecnológica de Colombia, 2022)
The objective of this article is to study the significance held by the Antonio Mijares main square for the inhabitants of SanJosé del Cabo as a central location of sociability. This work uses a qualitative methodology based on unstructured interviews with key individuals who are dedicated to promoting local culture and in situ observation, understanding that the public space is a location where citizens can interact, creating an environment of social interaction and of habitus, where people can seek recreation, attend civic, artistic, and cultural events, and where the ties of unity can be strengthened among thecitizens. It is concluded that the space studied, although in a process of touristification since 1974, as a result of the public policies on tourism, with the surrounding buildings mainly selling goods and services to foreign tourists, the society has appropriated the square, giving it a communal feel, encouraged by social, cultural and political manifestations by the local population.